(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of the research is to reveal the role and importance of cultural tourism in the tourism industry in Uzbekistan during the years of the Soviet Union. The time limit includes the years 1924-1991. The research work was analyzed on the basis of comparative-gradual, periodical methods based on foreign sources and newspapers and magazines published during the years of the Soviet Union. The analysis methods of scientists as V.A. Kvartalniy, G.A. Papirian, B.C. Malyshev, R. Yu. Popova, O.P. Berezkin, N.V. Mikhailova, I.I. Ilina are given. The emergence of tourism in Uzbekistan falls directly on 20s of the 20th century in the Soviet Union and served as a tool for the organization of recreation for workers and communist ideology. However, due to the lack of tourism infrastructure during this period, the Soviet Union was forced to put up an artificial barrier to the flow of foreign tourists.